PENGOLAHAN PANGAN LOKAL: DEMO MASAK CANDIL UBI UNGU RENDAH GULA UNTUK PENCEGAHAN DIABETES DI DESA GUNUNG RAJA - Anggun Kelara; Devi Ardila; Elni Kartika; Ingwer Ludwig Partogi Nahulae; Marisa Marisa; Nadya Selfa; Najwa Adilla Rahmania; Poppy Dearisa Putri; Resty Adellia Asmarani; Rieke Rahma Dwinda; Rima Mutiara; Rizka Fadila; Vatma Pratiwi (Departement of Environmental Health, Faculty of Public Health, Sriwijaya University, 2026)
Local food is food that grows and is available in the local area. One example of potential local food is purple sweet potato, which is rich in fiber and antioxidants that make purple sweet potato a good food for diabetes prevention through cooking demonstrations. The goal was to improve the skills of the community in making healthy snacks made from local food purple sweet potato. The method used was participatory education in the form of cooking demonstrations. As a result, the participants were able to do a cooking demonstration of making purple sweet potato candies independently, they were also enthusiastic about participating in the activity. The conclusion is that the skills of the community in making healthy snacks made from local food purple sweet potato and increasing the awareness of the Gunung Raja Village community about the importance of diabetes prevention.